Investigation of effective conservation measures for the critically endangered White-bellied Heron Ardea insignis using an integrated population model and Bayesian population viability analysis - Indra P. Acharja; Yuji Okahisa; M. Clay Green; Tshewang Lhendup; Sonam Tshering; Thinley Phuntsho; Tshering Tobgay; Lungten Lungten; Jigme Tshering; Samten Leki (Avian Conservation and Ecology, 2025)
Although conservation efforts worldwide have transitioned toward landscape and regional approaches, species such as the White-bellied Heron Ardea insignis still require targeted actions because of their extremely small and declining population size and restricted distribution. In situations where every individual bird is critical to the population, conservation actions must be precise and effective, leaving little margin for error. Despite commendable conservation measures for the White-bellied Heron, especially in Bhutan, where a major population is found, the declining population trend is alarming, necessitating both short-term and long-term conservation strategies. This study sought to propose a measure to conserve the species by analyzing two decades of population, breeding, and mortality data using a Bayesian population viability analysis and integrated population model. Our analysis revealed that the annual survival rates of juveniles are remarkably low, and without new conservation measures, the population is expected to continue declining with high certainty. Under the current scenario, our models predict extinction probabilities between 10.4 and 26.6%, whereas the probabilities of population increase are only 6.2 to 14.0% for the next 30 years. Our models suggest that increasing juvenile survival rates by 20% and supplementing the wild population by releasing at least five captive-bred birds annually would improve the probability of population growth by 99% over the next 30 years. The newly established, White-bellied Heron Conservation Center will play a critical role in conserving the species through the provision of captive bred birds via the collection of eggs and chicks and raising them in captivity. The captive breeding program would provide a healthy breeding stock and representative genetic diversity, while at the same time, more chicks could be saved by raising them for the first year and safely releasing them back the following winter when the river volumes are low, and feeding grounds are comparatively safe and abundant. This would also enable breeding pairs to re-clutch and produce a second brood the same year. However, identifying and addressing the major cause of juvenile mortality and threats hindering wild population growth is crucial for reestablishing a self-sustaining wild population. This study demonstrates how limited and fragmented information can still be effectively utilized to make informed decisions for conserving vulnerable species in countries facing challenges in comprehensive research and monitoring.